Evaluation of anti-osteoarthritic activity of Vigna mungo in papain induced osteoarthritis model - Patel, Dhaval V. (Indian J Pharmacol, 2015)
AIM: This study was carried out to evaluate the effect of Vigna mungo hydroalcoholic extract (VMHA) by papain induced osteoarthritis (OA) in the rat model. MATERIALS AND METHODS: OA was induced by intra-articular injection of papain (4% w/v) along with cysteine (0.03 M) on day 1, 4 and 7 in rats and VMHA was administered orally in three doses (100, 200 and 400 mg/kg) after last papain injection. The anti-osteoarthritic activity was evaluated by measuring knee joint diameter, grip strength, locomotion activity and hanging time. Histopathological analysis and acute toxicity study were also performed. RESULTS: VMHA improved inflammatory condition with all the doses, but significant (P < 0.05) attenuation of inflammation was present only with 400 mg/kg dose. The grip strength, locomotion activity and hanging time were also significantly (P < 0.05) improved at dose level of 100 mg/kg however other two doses (200 mg/kg and 400 mg/kg) were not found to be effective. VMHA did not show any mortality or any toxic clinical signs after oral administration of 2 g/kg dose. CONCLUSION: VMHA improved arthritic condition by significantly reducing pain and inflammation.